Effects of the Herbal Soft Gel Capsule Containing Pimpinella Anisum, Oenothera Biennis, and Salvia Sclarea Oils on Premenstrual Syndrome: A Triple-blinded Randomized Controlled Trial Study - Simbar, Masoumeh; Mahboubi, Mohaddese; Nazarpour, Soheila; Majd, Hamid Alavi; Kiani, Zahra; Fakari, Farzaneh Rashidi; Khorrami, Mobina; Keyvanfar, Sepideh; Saberi, Naiereh (Current Traditional Medicine, 2026)
ObjectivePremenstrual syndrome (PMS) is a combination of physical and psychological symptoms that start during the luteal phase. There are no specific effective and safe remedies to relieve these symptoms. However, there is a great tendency to use herbal medicines instead of chemical medicines. This study aimed to assess and compare the effects of a soft gel capsule containing Pimpinella anisum, Oenothera biennis, and Salvia sclarea oils (POS) with control, before and after use in two consecutive cycles, on physical and psychological symptoms of PMS.MethodsThis was a triple-blind randomized clinical trial performed on 67 female students, who were residents in dormitories of the Shahid Beheshti University of Medical Science in Tehran, Iran. The participants were randomly divided into two groups: soft gel capsule users containing POS as the intervention group (n=32) and sunflower as the control group (SF) (n=35). The participants were 18-35 years old female students who were affected by PMS. The capsules were used twice daily, from the 21st day of the menstrual cycle to 2 days after the menstruation, for two consecutive menstrual cycles. The tools for data collection were three questionnaires: a personal information questionnaire, a valid and reliable daily PMS symptom report (DSR) form, and a side effects assessment questionnaire. The physical, psychological, and general symptoms of PMS were assessed by the DSR, and the results were taken before and after intervention and between groups of the study.ResultsBefore and after the intervention, the comparison showed significant effectiveness of POC in reducing general, physical, and psychological symptoms after the first and second months of use. However, the comparison of the groups did not show a significant difference between the two groups regarding their PMS symptoms and the side effects of the medicines (p<0.05).ConclusionPOS is a combination of three herbal medicines effective on the symptoms of premenstrual syndrome, which can be used effectively and safely to improve the physical and psychological symptoms of premenstrual syndrome. This herbal remedy can be recommended by health care providers to women, who suffer from PMS symptoms and prefer to use herbal remedies instead of synthetic drugs. Further studies are necessary to evaluate the combined herbal remedies as well as the effectiveness of sunflower oil on PMS symptoms.Clinical Trial Registration No.IRCT20190306042943N1.
Keywords: Pimpinella anisum